2012
DOI: 10.1111/j.1463-1318.2010.02487.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation of the residual appendix stump: a systematic review

Abstract: Stump appendicitis is rare. It may complicate open or laparoscopic appendicectomy. A high level of suspicion should be maintained in any patient with right sided abdominal pain and a history of prior appendicectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…15 Suspicion of the condition and prompt diagnosis can potentially reduce the risk of serious complications because of delayed treatment (perforation, abscess formation), or misdiagnosis (constipation, gastroenteritis). 10 The short interval between surgery and ultrasound in the two cases we have described suggests that the findings were likely from persistent inflammation from the initial appendicitis rather than to new inflammation of the appendiceal stump. Whilst the diagnosis in our second case was confirmed surgically, the first resolved after conservative management.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…15 Suspicion of the condition and prompt diagnosis can potentially reduce the risk of serious complications because of delayed treatment (perforation, abscess formation), or misdiagnosis (constipation, gastroenteritis). 10 The short interval between surgery and ultrasound in the two cases we have described suggests that the findings were likely from persistent inflammation from the initial appendicitis rather than to new inflammation of the appendiceal stump. Whilst the diagnosis in our second case was confirmed surgically, the first resolved after conservative management.…”
Section: Discussionmentioning
confidence: 74%
“…Inflammation of the base or stump of a surgically removed appendix is an uncommon, and likely under‐recognised condition in both children and adults with cases reported in patients aged between 8 and 72 years of age . The paucity of documented cases in the literature make it difficult to determine its incidence, although it is estimated to occur in 1:50 000 appendicectomy patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the most recent comprehensive review of the literature examining thirty-six (36) cases of stump appendicitis by Liang et al 3 revealed that only 34% of cases were initially performed laparoscopically, and 66% were initially performed as open surgeries, thereby, supporting that it can occur after ei ther laparoscopic or open appendectomy. 19 Stump appendicitis is a real entity not often considered when evaluating patients with ri ght lower quadrant abdominal pain after appendectomy and may be probably an underreported problem. 20,21 It can occur from about two weeks to an interval of twenty-three year after appendectomy but our case presented four and half months postlaparoscopic appendicectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most recent comprehensive review of the literature examining thirty-six (36) cases of stump appendicitis by Liang et al [3] revealed that only 34% of cases were initially performed laparoscopically, and 66% were initially performed as open surgeries, thereby, supporting that it can occur after either laparoscopic or open appendectomy [19]. …”
Section: Discussionmentioning
confidence: 99%